Education and gastric cancer risk—An individual participant data meta‐analysis in the StoP project consortium. Issue 3 (10th April 2019) - Rota, Matteo; Alicandro, Gianfranco; Pelucchi, Claudio; Bonzi, Rossella; Bertuccio, Paola; Hu, Jinfu; Zhang, Zuo‐Feng; Johnson, Kenneth C.; Palli, Domenico; Ferraroni, Monica; Yu, Guo‐Pei; Galeone, Carlotta; et al.
Abstract : Low socioeconomic position (SEP) is a strong risk factor for incidence and premature mortality from several cancers. Our study aimed at quantifying the association between SEP and gastric cancer (GC) risk through an individual participant data meta‐analysis within the "Stomach cancer Pooling (StoP) Project". Educational level and household income were used as proxies for the SEP. We estimated pooled odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) across levels of education and household income by pooling study‐specific ORs through random‐effects meta‐analytic models. The relative index of inequality (RII) was also computed. A total of 9, 773 GC cases and 24, 373 controls from 25 studies from Europe, Asia and America were included. The pooled OR for the highest compared to the lowest level of education was 0.60 (95% CI, 0.44–0.84), while the pooled RII was 0.45 (95% CI, 0.29–0.69). A strong inverse association was observed both for noncardia (OR 0.39, 95% CI, 0.22–0.70) and cardia GC (OR 0.47, 95% CI, 0.22–0.99). The relation was stronger among H. pylori negative subjects (RII 0.14, 95% CI, 0.04–0.48) as compared to H. pylori positive ones (RII 0.29, 95% CI, 0.10–0.84), in the absence of a significant interaction ( p = 0.28). The highest household income category showed a pooled OR of 0.65 (95% CI, 0.48–0.89), while the corresponding RII was 0.40 (95% CI, 0.22–0.72). Our collaborative pooled‐analysis showed a strong inverse relationship between SEP indicators and GC risk. Our data call for public health interventions to reduce GC risk among the more vulnerable groups of the population. Abstract : What's new? Gastric cancer is associated with low socioeconomic position but the precise impact of education on gastric cancer risk needs to be quantified. Here the authors provide an updated quantification through the analysis of the Stomach cancer Pooling (StoP) Project, a large international consortium of case‐control studies. They observe a 40% decreased risk of gastric cancer among individuals with intermediate/high education status as compared to less educated study subjects. The association was evident regardless of Helicobacter pylori infection, underscoring the need for public health interventions to reduce gastric cancer risk.